The role of neurohormonal blockers in the primary prevention of acute-, early-, and late-onset anthracycline-induced cardiotoxicity - Ahmed Ayuna; Nik Abidin (The Egyptian Heart Journal, 2020)
Abstract Background Anthracycline-induced cardiotoxicity has been classified based on its onset into acute, early, and late. It may have a significant burden on the quality and quantity of life of those exposed to this class of medication. Currently, there are several ongoing debates on the role of different measures in the primary prevention of cardiotoxicity in cancer survivors. Our article aims to focus on the role of neurohormonal blockers in the primary prevention of anthracycline-induced cardiotoxicity, whether it is acute, early, or late onset. Main body of the abstract PubMed and Google Scholar database were searched for the relevant articles; we reviewed and appraised 15 RCTs, and we found that angiotensin-converting enzyme inhibitors (ACEI) and B-blockers were the most commonly used agents. Angiotensin II receptor blockers (ARBs) and mineralocorticoid receptor antagonists (MRAs) were used in a few other trials. The follow-up period was on the range of 1–156 weeks (mode 26 weeks). Left ventricular ejection fraction (LVEF), left ventricular diameters, and diastolic function were assessed by either echocardiogram or occasionally by cardiac magnetic resonance imaging (MRI). The occurrence of myocardial injury was assessed by troponin I. It was obvious that neurohormonal blockers reduced the occurrence of LVEF and myocardial injury in 14/15 RCTs. Short conclusion Beta-blockers, especially carvedilol and ACEI, especially enalapril, should be considered for the primary prevention of acute- and early-onset cardiotoxicity. ARB and MRA are suitable alternatives when patients are intolerant to ACE-I and B-blockers. We recommend further studies to explore and establish the role of neurohormonal blockers in the primary prevention of the acute-, early-, and late-onset cardiotoxicity.